Creating jobs through the IDC's UIF fund - Xaba, Masodi Nkosazana (My University, 2015)
Unemployment is one of the social ills facing South African society and unless a concerted effort to drive job creation and save existing jobs is accelerated, poverty, inequality and unemployment will continue to ravage our nation for a long time. The study explores the job creation and job saving objectives of the IDC’s UIF fund in Gauteng and investigates the types of jobs created. The UIF is a fund established by government to fund enterprises that commit to job creation and to save existing jobs. The research adopted a qualitative research methodology with data collected through document analysis and by interviewing the funds’ beneficiary enterprises. The findings reveal that the performance of these enterprises in creating and saving jobs has had a minimal net job creation effect. The study revealed that the size of enterprise had no bearing on job creation as 77.8% of enterprises across all stages of development have experienced negative jobs growth. It also found that the IDC’s UIF fund has not evolved with the changing nature of work in its definition of jobs created as it has not taken into account the jobs created through externalisation. The study further revealed that start-up enterprises struggled to create good jobs in line with the decent work agenda as more than one characteristic of the decent was not met in an enterprise. Government and policy makers need to address the hurdles that stand in the way of accelerating job creation and job saving endeavours, failing which, the intervention strategies it employs will be fruitless. The study further sought to understand the role played by the IDC in the realisation of the IDC’s UIF fund objectives. The research found that the IDC’s role is limited to financial support and has not been extended to non-financial support needed by enterprises.
Thesis (M.M. (Public & Development Management))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Governance, 2015.